Customizing IBM Tivoli Workload Scheduler for z/OS V8.2 to improve performance - Gucer, Vasfi (IBM redbooks., 2004)
Scheduling is generally considered as the nucleus of the data center, because the orderly, reliable sequencing and management of process execution is an essential part of IT management. IBM Tivoli Workload Scheduler for z/OS is the IBM strategic product used in many large-to-midsized customer environments, responsible for scheduling critical batch applications. Therefore, the performance of Tivoli Workload Scheduler for z/OS is one of the important factors that affect the overall satisfaction from the IT services for these companies. This IBM Redbooks publication covers the techniques that can be used to improve performance of Tivoli Workload Scheduler for z/OS (including end-to-end scheduling). There are many factors that might affect the performance of any subsystem. In this book, we confine ourselves to those things that are internal to Tivoli Workload Scheduler, or can be easily verified and modified, and are likely to apply to the majority of Tivoli Workload Scheduler customer sites. Although this book is aimed at those very large installations with a batch load of 100,000 or more jobs per day, it will also be relevant to installations with a smaller batch workload who are suffering from a shrinking batch window, or those who are trying to maximize the throughput on their existing hardware, or both. Please note that the additional material referenced in the text is not available from IBM.